2021
DOI: 10.2174/1570162x18999200819172009
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Strategies Towards the Elimination of Latent HIV-1 and Subsequent HIV-1 Cure

Abstract: Background: During the past 35 years, highly effective ART has saved the lives of millions of people worldwide by suppressing viruses to undetectable levels. However, this does not translate to the absence of viruses in the body as HIV persists in latent reservoirs. Indeed, rebounded HIV has been recently observed in the Mississippi and California infants previously thought to have been cured. Hence, much remains to be learned about HIV latency, and the search for the best strategy to eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 116 publications
(150 reference statements)
0
12
0
Order By: Relevance
“…The activation of these resting cells, particularly after prolonged periods of dormancy, results in proviral gene expression of HIV-1 and consequent renewal of viral infection [ 103 ]. The increasing emphasis has therefore been on exploring therapeutic interventions aimed at complete elimination of the latent proviruses (sterilized cure) [ 104 ]. Of particular research interest is what is commonly termed as the ‘shock and kill’ strategies, whereby the transcription of HIV-1 proviruses present in resting CD4+ T reservoir cells is de-repressed with the aid of small molecule drugs for the production of replicating virus, which could be inhibited through simultaneous administration of highly active antiretroviral therapy (HAART) [ 105 ].…”
Section: Marine Bioactive Peptides (Mbaps)mentioning
confidence: 99%
“…The activation of these resting cells, particularly after prolonged periods of dormancy, results in proviral gene expression of HIV-1 and consequent renewal of viral infection [ 103 ]. The increasing emphasis has therefore been on exploring therapeutic interventions aimed at complete elimination of the latent proviruses (sterilized cure) [ 104 ]. Of particular research interest is what is commonly termed as the ‘shock and kill’ strategies, whereby the transcription of HIV-1 proviruses present in resting CD4+ T reservoir cells is de-repressed with the aid of small molecule drugs for the production of replicating virus, which could be inhibited through simultaneous administration of highly active antiretroviral therapy (HAART) [ 105 ].…”
Section: Marine Bioactive Peptides (Mbaps)mentioning
confidence: 99%
“…In addition to these strategies, the "Shock and Kill" approach to reducing the size of reservoirs is a current challenge, whereby latency-reversing agents (LRAs) reactivate latently infected provirus (the shock) and induce cell death mediated by cytopathic effects, apoptosis, or CTL response (the kill), combined with ART treatment to prevent the occurrence of a new infection. This strategy is still under development (108), and some small-molecule chemical compounds, including histone deacetylase inhibitors (HDACi) (e.g., SAHA/vorinostat) (109), bromodomain and extraterminal domain inhibitors (BETi) (e.g., JQ1) (110), and protein kinase C (PKC) agonists [e.g., Prostratin, PEP-005 (ingenole-3-angelate) and bryostatin-1] (111), are being intensively investigated as candidate LRAs. Several groups have reported that using an LRA, active via a single mechanism, might not lead to effective viral reactivation in reservoir cells, and combinations of drug candidates with different mechanisms of action will be needed to enhance proviral activation.…”
Section: The Current Approach Towards Hiv-1 Eradicationmentioning
confidence: 99%
“…Several groups have reported that using an LRA, active via a single mechanism, might not lead to effective viral reactivation in reservoir cells, and combinations of drug candidates with different mechanisms of action will be needed to enhance proviral activation. Currently, combining the BRD4 inhibitor (JQ1) and PKC agonist(s) (e.g., Prostratin, PEP-005) might be the most effective means of reactivating the HIV-1 provirus (7,108). Despite the potent effects of LRA or a combination of LRAs on ex vivo or in vitro analyses, multiple clinical trials have failed to reduce latent reservoir size sufficiently, and none have shown superior therapeutic effects compared with current cART (112).…”
Section: The Current Approach Towards Hiv-1 Eradicationmentioning
confidence: 99%
“…Enormous reductions have been observed in rates of death and suffering when use is made of a potent ARV regimen, particularly in the early stages of the disease. However, there is still no cure for HIV infection, given the promises utilizing HAART and/or stem cell transplantation [ 1 , 2 ]. T cells play a crucial role in HIV infection; a robust T-cell response is associated with control of HIV infection; however, HIV-specific T cells are deleted or dysfunctional in HIV/AIDS [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%